Sosialisasi Meningkatkan Minat Baca pada Anak-anak dan Remaja - Alfirah; Ananda Hadi Elyas; Muhammad Eka (Jurnal Pengabdian Masyarakat, 2022)
Literacy is basically a person's ability to understand, process and communicate information received through reading and writing activities. This ability will then be used to find information in solving problems that exist in everyday life. Literacy ability is very identical with the daily life of society. Starting when a child can recognize various kinds of symbols, pictures, numbers, writing, instructions, until he is able to assemble letters into sentences that contain meaning. This literacy has started in people's lives so it must be brought back so that it does not experience fading and disappears slowly. A country will progress because of knowledge. Adolescents who already have an interest in reading will certainly have broad insights and knowledge. Knowledgeable teenagers will be able to become good successor assets and be able to prosper their environment and even a country. The existence of books for the younger generation at this time is not only as an item to memorize, but also as a form of insight that can help people to know themselves more deeply, understand about social dynamics, to get to know the whole world. With this the community service team intends to hold outreach to increase children's and youth's interest in reading and raise awareness of the importance of the benefits of reading.